SPECTRAL ALBEDO OBSERVATION ON THE SNOW FIELD AT BARROW, ALASKA - アオキ, テルオ; アオキ, タダオ; フカボリ, マサシ; タチバナ, ヨシヒロ; ザイゼン, ユウジ; ニシオ, フミヒコ; オイシ, トモヒコ; AOKI, Teruo; AOKI, Tadao; FUKABORI, Masashi; TACHIBANA, Yoshihiro; ZAIZEN, Yuji; et al. (National Institute of Polar Research, 1998)
P(論文) Spectral albedo observation at the visible and near infrared wavelengths was carried out on the snow field at Barrow. Alaska in April, 1997. The data are compared with the theoretical calculations made by a multiple scattering radiative transfer model for the atmosphere-snow system using the snow physical parameters observed by snow pit work. It is found that the optically effective snow grain size is on the order of branch size for new snow consisting of dendrites, but is not of the crystal size. The observed spectral albedo was lower than theoretically calculated for "pure snow" in the visible and a part of the near infrared; such reduction is explained by the internal mixture of soot and external mixture of dust for snow particles. The theoretical spectral albedo calculated for a two-layer snow model that contains impurities agrees very well with the observations at all wavelengths. departmental bulletin paper